MERANGKAI PUZZLE: PELATIHAN MANAJEMEN PROYEK SEDERHANA UNTUK AKTIVIS ORGANISASI SISWA INTRA SEKOLAH - Simanjorang, Jeffri Yosep; Monim, Oktovina Hanani Kristin; Maulidza, Muhammad; Bessie, Loudewyk Marcelano Leyriz; Wicaksono, Kristian Widya (STKIP Pesisir Selatan, 2025)
This article documents a training programme on basic project management for Intra-School Student Organisation (OSIS) - the official student body in Indonesian secondary schools- committee members, conducted in 2024. OSIS serves as a platform for student capacity building through various programmes. While OSIS is encouraged to organise numerous activities, training in project management for its committee members remains relatively scarce. In response to this gap, the training aimed to enhance OSIS committee members' project management skills. The training materials were adapted from the logical framework approach, with simplified terminology to facilitate student comprehension. A puzzle-based learning approach was employed to introduce project management concepts. This initiative involved 70 OSIS committee members from seven schools across West Java, Central Java, and the Special Region of Yogyakarta. Evaluation was conducted through pre-test and post-test surveys, supplemented by facilitator observations. The findings indicated a significant improvement in participants' understanding of basic project management.